Cuticle and pore plug properties in the table egg - Kulshreshtha, G; Rodriguez-Navarro, A; Sanchez-Rodriguez, E; Diep, T; Hincke, M T (Poultry science, 2018)
Food safety of table eggs is vital since many pathogens can contaminate the unfertilized egg, leading to increased risk of foodborne illness for consumers. The eggshell cuticle is the first line of defense to restrict the entry of egg-associated pathogens, such as Salmonella Enteritidis. The thickness and completeness of coverage of the cuticle layer are heritable traits that are strongly associated with egg resistance to bacterial penetration. The present study characterizes the chemical composition of the eggshell cuticle and structure of pore plugs from table eggs. Eggs collected from both brown and white egg laying Lohmann flocks (early, mid, and late lay) were either unwashed or washed. Pore plugs were characterized using scanning electron microscopy (SEM), and elemental composition was determined using energy-dispersive x-ray spectroscopy (EDS). SEM observations confirmed that the plug formed by the cuticle layer within the eggshell pore remains firmly lodged throughout the commercial washing process. The eggshell thickness and cuticle pore length visualized in brown eggs was significantly higher than in white eggs in hens of all ages. EDS analysis revealed that the pore inner surface was enriched in phosphorus and chemically different from the surrounding bulk eggshell mineral. Detailed assessment of the cuticle chemical composition was performed by Fourier transform infrared spectroscopy (FTIR). Washing of eggs removed cuticle from the eggshell surface. There was a trend of lower cuticle coverage with increasing hen age for white eggs. A significant reduction in the amount of proteins and phosphates and polysaccharides was observed in the cuticle of brown unwashed eggs with hen age. In white unwashed eggs, amides and lipids decreased with hen age; by contrast, the amount of sulfate was highest at mid-lay. The results from our research will assist selective breeding programs that target cuticle integrity and pore plug stability to enhance egg resistance to pathogen penetration and improve food safety.